The Formalization of Islamic Attire for Students: Differentiation of Discrimination and Intolerance Paradigms in the Case of Perkada Sharia in West Sumatra - Jarudin Jarudin; Hermawati Hermawati; Walan Yudhiani; Alfi Syukri Rama; Muhammad Adib bin Samsudin (JURIS (Jurnal Ilmiah Syariah), 2023)
The law on regional autonomy enacted by the central government is like the horns of a dilemma. The central government considers the formalization of religious aspects as a threat to national and state stability, as demonstrated by regional head regulations (Perkada) requiring students in West Sumatra to wear a veil or hijab. This qualitative research employed interviews, observation, and a study of the Supreme Court decision document No. 17/P/HUM/2021. Data were analyzed using normative juridical approaches and Islamic law through several stages, including data reduction, data display, and verification. This research found that the case arose as a result of an allegation that the school forced non-Muslim students to wear veils, which went viral on social media. In response to this allegation, the central government issued a Joint Decree (SKB) of Three Ministers canceling Perkada Number 451.442/BINSOS-III/2005. LKAAM, the customary holder of the Minangkabau community in West Sumatra, then petitioned the Supreme Court for a judicial review. The Supreme Court granted the LKAAM's request, ruling that the SKB was invalid and ordering the three ministries to revoke it. This case's substance alludes to at least two types of debate. First, the three ministers assumed the petitioner and the Supreme Court had no legal standing, while the Supreme Court's decision stated otherwise. Second, the central government viewed the people of West Sumatra through their local government as discriminatory, intolerant, ignoring children's religious aspirations, and ignoring higher regulations, whereas the Supreme Court decision contradicted the three ministers' arguments and supported the LKAAM argument. As a result, LKAAM won legally but not necessarily politically because the central government had labeled the people of West Sumatra as discriminatory and intolerant.